Utilizing Fcepsilon-Bak chimeric protein for studying IgE-FcepsilonRI interactions - Belostotsky, Ruth (Clinical immunology (Orlando, Fla.), 2004)
We previously constructed a pro-apoptotic Fcepsilon-Bak chimeric protein, targeted against cells expressing the IgE high affinity receptor (FcepsilonRI). We demonstrated that the chimeric protein is internalized by target mast cells and kills them. These results, which constitute a promising basis for applying this approach to antiallergic therapy, raise some theoretical questions with respect to two major issues: (a) is the monomeric Fcepsilon-Bak-FcepsilonRI complex able to undergo endocytosis, and (b) does the receptor binding domain of human IgE (Fcepsilon) react with rodent FcepsilonRI? In an attempt to answer these questions, we have now thoroughly investigate the interaction of human (h) and mouse (m) Fcepsilon-Bak with FcepsilonRI-positive cells. Using established cultures of rodent and human origin, as well as a primary mouse mast cell culture, we demonstrate that binding of the chimeric protein to the membrane is followed by quick endocytosis, leading to the apoptosis of specific cells. We also confirm that this interaction depends on FcepsilonRI and not on other IgE receptors. We found that the effect of Fcepsilon-Bak on the cells depends on the level of surface FcepsilonRI expression, but not on the origin of the target cells or of the Fcepsilon moiety. We suggest that endocytosis of the monomeric Fcepsilon-Bak-FcepsilonRI complex results from the inability of Fcepsilon-Bak to transduce signals, characteristic of the monomeric IgE-FcepsilonRI complex due to the absence of the variable portion of the IgE molecule. Our results also indicate that at least the Fc fragment of human IgE is able to interact with both human and rodent FcRI